PD-L1 expression and mismatch repair deficiency in locally advanced head and neck squamous cell carcinoma treated with chemoradiotherapy: association with treatment response and survival - Zhang, Bingyi; Guo, Dong; Hou, Yujuan; Wei, Xinyue; Cai, Yuanyuan; Sun, Daqing; Wang, Xiaoxiao; Wang, Xiaoli; Li, Jianwen; Hao, Furong (Frontiers in Immunology, 2026)
BackgroundConcurrent chemoradiotherapy (CCRT) served as the cornerstone of definitive treatment for locally advanced head and neck squamous cell carcinoma (LA-HNSCC), yet there was heterogeneity in patients’ treatment responses. This study aimed to evaluate the clinical significance of programmed death ligand-1 (PD-L1) expression and deficient mismatch repair (dMMR) as predictive markers of response to CCRT in patients with LA-HNSCC.MethodsThis study retrospectively analyzed 156 cases of LA-HNSCC patients who received CCRT treatment at our hospital from January 2020 to April 2024. All patients received intensity-modulated radiotherapy with concurrent chemotherapy. PD-L1 expression was assessed using immunohistochemistry and quantified with the Combined Positive Score (CPS). Mismatch repair status was evaluated using antibodies against MLH1, PMS2, MSH2, and MSH6. The treatment response was assessed according to the Response Evaluation Criteria In Solid Tumors version 1.1 (RECIST 1.1).ResultsThis study included a total of 156 patients with LA-HNSCC, with a male predominance (125 cases). The deficient mismatch repair (dMMR) prevalence was 6.4% (10/156), and high PD-L1 expression (CPS≥20) was observed in 47.4% (74/156) of patients. There was a significant association between high PD-L1 expression and an increased objective response rate to CCRT (97.1% compared to 58.5%, P<0.001). Conversely, patients with dMMR exhibited a reduced response rate (50.0% versus 79.5%, P = 0.031). In the survival analysis, patients with high PD-L1 expression demonstrated significantly longer overall survival (OS) (P = 0.0021) and progression-free survival (PFS) (P<0.001). In contrast, dMMR status was not significantly associated with OS or PFS. Multivariate analysis identified smoking (HR = 6.871, 95%CI: 2.214-21.32, P<0.001) and high PD-L1 expression (HR = 2.591, 95%CI: 1.036-6.483, P = 0.042) as independent risk factors for OS.ConclusionThe study confirmed that high PD-L1 expression was a positive biomarker for predicting the benefit of CCRT in patients with LA-HNSCC. Although dMMR was associated with initial treatment resistance, its unique immunogenicity was found to influence disease progression and subsequent treatment options. These findings suggested that MMR testing in LA-HNSCC patients had significant clinical value, not only aiding in the identification of patients who might benefit from subsequent immunotherapy but also potentially informing initial treatment strategies, such as the prospective exploration of combined immunotherapy approaches.